2016
DOI: 10.3390/ma9090763
|View full text |Cite
|
Sign up to set email alerts
|

Novel Osteointegrative Sr-Substituted Apatitic Cements Enriched with Alginate

Abstract: The present work describes the synthesis of novel injectable, self-setting bone cements made of strontium-substituted hydroxyapatite (Sr-HA), obtained by single-phase calcium phosphate precursors doped with different amounts of strontium and enriched with alginate. The addition of alginate improved the injectability, cohesion, and compression strength of the cements, without affecting the hardening process. A Sr-HA cement exhibiting adequate hardening times and mechanical strength for clinical applications was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 62 publications
(86 reference statements)
0
28
0
Order By: Relevance
“…The injectable biomaterials represent an excellent strategy to improve the interaction of the material itself with the surrounding tissues in osteoporotic patients [ 29 31 ]. In the present study, it has been demonstrated that novel injectable strontium-doped apatitic bone cements [ 22 ], influenced the viability, morphology and gene expression profiling of bone cells. A detailed morphological analysis showed MSCs and OBs well attached and spread on all the cement surfaces with their characteristic morphology.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The injectable biomaterials represent an excellent strategy to improve the interaction of the material itself with the surrounding tissues in osteoporotic patients [ 29 31 ]. In the present study, it has been demonstrated that novel injectable strontium-doped apatitic bone cements [ 22 ], influenced the viability, morphology and gene expression profiling of bone cells. A detailed morphological analysis showed MSCs and OBs well attached and spread on all the cement surfaces with their characteristic morphology.…”
Section: Discussionmentioning
confidence: 94%
“…Sr-doped HA cements were prepared as reported in our previous work [ 22 ]. Briefly, Sr-substituted αTCP powders with different strontium content (i.e.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of these results, a selected Sr-HA cement formulation was further tested in vivo in a rabbit model by compositional, morphological, and histological/histomorphometric analysis. The cement exhibited complete transformation into HA, thus showing a biomimetic composition, and enhanced the ability to induce new bone formation and penetration, provided also by its porous microstructure [65].…”
Section: Injectable Self-hardening Bone Cements With Biomimetic Compomentioning
confidence: 98%
“…Calcium phosphates are also the base of inorganic bone cements with good osteoinductive potential ( Dorozhkin, 2008 ; Boanini et al, 2010 ; Bohner, 2010 ; Schumacher et al, 2013 ; Sprio et al, 2016a ). An important advantage of calcium phosphate cements is the ability of self-hardening by dissolution/reprecipitation processes occurring in vivo at body temperature that yields the transformation of metastable calcium phosphates into calcium-deficient HA with acicular morphology.…”
Section: Biomaterials For Bone Tissue Applicationsmentioning
confidence: 99%